2013
DOI: 10.1371/journal.pone.0072648
|View full text |Cite
|
Sign up to set email alerts
|

Adenosine-Mediated Enteric Neuromuscular Function Is Affected during Herpes Simplex Virus Type 1 Infection of Rat Enteric Nervous System

Abstract: Adenosine plays an important role in regulating intestinal motility and inflammatory processes. Previous studies in rodent models have demonstrated that adenosine metabolism and signalling are altered during chronic intestinal inflammatory diseases. However, the involvement of the adenosinergic system in the pathophysiology of gut dysmotility associated to a primary neurodysfunction is still unclear. Recently, we showed that the neurotropic Herpes simplex virus type-1 (HSV-1), orally inoculated to rodents, inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 41 publications
3
28
0
Order By: Relevance
“…Contractility studies were performed as previously described (Giron et al, ; Brun et al, ; Zoppellaro et al, ). Segments (1 cm in length) of mouse distal ileum, proximal to the ileocaecal junction, were isolated and mounted along the longitudinal axis in organ baths containing 10 mL of oxygenated (95% O 2 and 5% CO 2 ) and heated (37°C) Krebs solution (in mM: NaCl 118, NaHCO 3 25, C 6 H 12 O 6 11, KCl 4.7, CaCl 2 ∙2H 2 O 2.5, MgSO 4 ∙1.2, K 2 HPO 4 1.2).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Contractility studies were performed as previously described (Giron et al, ; Brun et al, ; Zoppellaro et al, ). Segments (1 cm in length) of mouse distal ileum, proximal to the ileocaecal junction, were isolated and mounted along the longitudinal axis in organ baths containing 10 mL of oxygenated (95% O 2 and 5% CO 2 ) and heated (37°C) Krebs solution (in mM: NaCl 118, NaHCO 3 25, C 6 H 12 O 6 11, KCl 4.7, CaCl 2 ∙2H 2 O 2.5, MgSO 4 ∙1.2, K 2 HPO 4 1.2).…”
Section: Methodsmentioning
confidence: 99%
“…After 45 min equilibration, ileal segments were stretched passively to an initial tension of 0.5 g and brought to their optimal point of length‐tension relationship using 1 μM carbachol (Brun et al, ; Zoppellaro et al, ). Ileal segments were treated with carbachol to study cholinergic effects or with 60 mM KCl solution to elicit depolarization‐induced contraction.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Allergic diarrhoea, in a model of food allergy, was accompanied by chronic inflammation and mast cell hyperplasia in the colon [434], and it was suggested that sustained alteration in purinergic neurotransmission contributed to the disturbed motility characterised by this condition. Herpes simplex virus type-1 infects the enteric nervous system and affects gut motor function; contractions mediated by adenosine acting via A 1 or A 2A receptors on smooth muscle and A 2A and A 3 receptors in the myenteric plexus were impaired in virus-infected rats [764].…”
Section: Motility Disordersmentioning
confidence: 99%
“…Furthermore, viral infections alter or can be modulated by different components of the purinergic system, for example, NTPDase-6 (CD39L2) is required for foot-and-mouth disease virus replication (Piccone et al 2009), and uridine triphosphate (UTP) through interaction with purinergic receptors P2Y4 increases the production of antibodies against the rabies virus (Iwaki et al 2014). Furthermore, infection by herpes simplex virus may influence the adenosine metabolism by increasing adenosine deaminase and 5′-nucleotidase levels (Zoppellaro et al 2013), and adenosine deaminase inhibitors have been implicated in the in vitro reduction of HSV-1 replication (Williams and Lerner 1975). In addition, several studies have shown altered ectonucleotidase activity and expression associated with various pathologies (Trams and Lauter 1978;Glass et al 1996;Nagy et al 1997;Braun et al 1998;Lunkes et al 2004;Nedeljkovic et al 2006;Lavrnja et al 2009;Gandelman et al 2010).…”
Section: Discussionmentioning
confidence: 99%